10+p=3

Simple and best practice solution for 10+p=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+p=3 equation:


10+p=3

We simplify the equation to the form, which is simple to understand
10+p=3

We move all terms containing p to the left and all other terms to the right.
+1p=+3-10

We simplify left and right side of the equation.
+1p=-7

We divide both sides of the equation by 1 to get p.
p=-7

See similar equations:

| 6-2(4x)+7=0 | | 5(-2)=y+6 | | 7a*3a= | | 5(0)=y+6 | | 4-9p=49 | | 3/4+5/3 | | 5(2)=y+6 | | 9*n=53 | | 2y-6.2+y=8.8 | | -4+8X=5+2X | | 2(m+5)=28 | | 12+(21-6)/3 | | (4y+3)-(-3y-6)=-2 | | -2(6)+9=-(9)-3 | | -2(-12)+9=-(0)-3 | | 4(x-6)+2=6x-6 | | 5x-1+-2x+7=9 | | 65-98+(85-6x)=9 | | (9x^3-4x^2+3x)-(7x^2+2x+4)= | | 3x/4-21x/32=9/8 | | 12.4=9+t | | -2(2)+9=-(-4)-3 | | 4(y-1/2)=y-6(5-Y) | | 3x/4-21x/32=-11/8 | | 4=-5/x-6 | | 10x+28=4x+178 | | (9b-5)-4(2b+2)=-3 | | 4x-8=-11 | | -5(3)+15=-10(3) | | 5z+5=5z+5 | | 185-6x=30x+17 | | -5(-1)+15=-10(1) |

Equations solver categories